The synthetic cannabinoid WIN-55, 212 induced-apoptosis in cytotrophoblasts cells by a mechanism dependent on CB1 receptor. (15th June 2017) - Almada, Marta; Costa, Lia; Fonseca, Bruno Miguel; Amaral, Cristina; Teixeira, Natércia; Correia-da-Silva, Georgina
Abstract: The endocannabinoid system has evolved as a key regulator in several pathological and physiological processes, including placentation, decidualization and implantation. In addition, it is known that Cannabis and cannabinoids negatively affect female reproduction. Although, the biological action of synthetic cannabinoids, such as WIN-55, 212, in human fertility and pregnancy outcome remain to be unveiled. A tight balance between proliferation, differentiation and apoptosis of trophoblast cells is required for placental development and pregnancy outcome. Therefore, in this work, the effects of the synthetic cannabinoid WIN-55, 212 in placental cytotrophoblast cells were explored. For that, it was used a human choriocarcinoma cell line, BeWo cells, and primary cultures of human cytotrophoblasts isolated from term placentas. Results demonstrate that this synthetic cannabinoid induces cell cycle arrest. We also observed that cell viability loss was associated with a disruption of mitochondrial membrane potential and activation of caspases -9 and -3/-7 independently of reactive oxygen species (ROS) production or recruitment of the endoplasmic reticulum stress marker CHOP . Moreover, these effects were prevented by pre-incubation with a selective cannabinoid receptor 1 (CBR1) antagonist (AM281). Thus, our results provide strong evidences of the apoptotic process induced by WIN-55, 212 through the activation of the CBR1, which may reveal the impact of cannabinoids consumption during placental development.